2021
DOI: 10.1002/cepa.1467
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Fire Mechanical Properties of Steel S900MC

Abstract: This paper discusses mechanical properties after one heating and cooling cycle using experimental tests. The material tested was steel S900MC, which has the nominal yield strength of 900 N/mm2. The specimens were tested with being first heated up inside a furnace to a pre‐defined temperature, then cooled down to the room temperature. I n order to study the effects of cooling rates on mechanical properties, two different cooling methods were used: cooling inside furnace, and cooling in the air. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The truss beams had local temperatures as high as 1100°C and the cooled down temperatures as low as 200°C, but the vertical displacement did not exceed the displacement limit criterion demonstrating an efficient load redistribution in the truss beam system. The material tests in [16] showed that, when the steel was cooled from 700°C to 900°C to room temperature, it had about 40% and 20% retention in strength, respectively. Therefore, the effect of the reduced strength on the structural response after cooling stage as well as the effects of different heating-cooling-heating cycles on the strength reserve needs further research.…”
Section: Results: Structural Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The truss beams had local temperatures as high as 1100°C and the cooled down temperatures as low as 200°C, but the vertical displacement did not exceed the displacement limit criterion demonstrating an efficient load redistribution in the truss beam system. The material tests in [16] showed that, when the steel was cooled from 700°C to 900°C to room temperature, it had about 40% and 20% retention in strength, respectively. Therefore, the effect of the reduced strength on the structural response after cooling stage as well as the effects of different heating-cooling-heating cycles on the strength reserve needs further research.…”
Section: Results: Structural Analysismentioning
confidence: 99%
“…One of the defensive actions that can be adopted is structural cooling where the aim is to cool the load bearing elements to prevent structure failure. But as sudden cooling of structural elements at high temperatures (> 600°C) can result in significant change in material properties and load bearing capacity [16,17], it is unclear how the structural cooling affects the safety of the building. In large openframe buildings (floor area > 500 m 2 ) with unprotected structural elements, both the fire and the fire intervention may contribute to the risk of structural failure.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the behaviour of simple connections between composite beams and column in fire, two benchmark tests (CB-3 and CB-4) performed at Purdue University [17] were selected for creating FE models. The test setup and the specimen details are shown in Figure 1 and Figure 2.…”
Section: Benchmark Testsmentioning
confidence: 99%
“…The surface cooling or the gas cooling was intended to simulate the two cooling scenarios where either the structural member is cooled directly or the fire itself is cooled directly. A cooling rate of 40℃/min was selected as used in [17] for cooling the tensile coupon of S900 in air. The cyclic heating and cooling condition can occur in the travelling fire scenarios as reported in [5] or in applying the water sprays to the beam as reported in [6].…”
Section: Effects Of Different Fire Scenarios On Behavior Of Composite...mentioning
confidence: 99%